PENGEMBANGAN BAHAN AJAR MATEMATIKA DENGAN MODEL DISCOVERY LEARNING UNTUK MENGEMBANGKAN KETERAMPILAN BERPIKIR KRITIS - Deni Efendi (Eksponen, 2019)
This research aimed to find out the validity and effectivity of Discovery Learning Model-integrated mathematics instructional materials on SPLDV topic viewedthrough critical thinking skill improvement and percentage of students’ learning completion. It occupied Reserach and Development utilizing procedures established by Borg and Gall, with only performing up to main product revision. The research subject was students VIII G class of SMP Negeri 1 Seputih Agung, with moderate to high skill characteristic. Meanwhile, data of students’ critical thinking skill improvement were gained through pretest and posttest, using N-Gain test. Eventually, the research result pointed out that validation of mathematics instructional materials developed through Discovery Learning Model on SPLDV topic attained good and effective interpretation. It was seen through moderatecategorized calculation of N-Gain and accomplishment level of students’ learning result exceeding ideal accomplishment percentage (75%).